2020
DOI: 10.1155/2020/3965961
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Anesthesia Methods in Percutaneous Kyphoplasty for Treatment of Vertebral Compression Fractures

Abstract: Aim. Percutaneous kyphoplasty (PKP) is a routine operation for the treatment of vertebral compression fracture (VCF). Both local anesthesia and general anesthesia are widely used for PKP. However, which type of anesthesia is better for PKP still remains uncertain. This study aimed to find out whether local anesthesia or general anesthesia is more suitable for PKP. Methods. This is a retrospective clinical trial. A total of 85 single-level VCF patients who received PKP 12 months ago were recruited in this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…To minimize the effect on the general situation of elderly patients, PKP under local anesthesia is an effective method for treating OVFs [14][15][16][17][18]. Liu et al reported that local anesthesia for single vertebra PKP surgery can effectively relieve pain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To minimize the effect on the general situation of elderly patients, PKP under local anesthesia is an effective method for treating OVFs [14][15][16][17][18]. Liu et al reported that local anesthesia for single vertebra PKP surgery can effectively relieve pain.…”
Section: Discussionmentioning
confidence: 99%
“…Local anesthesia can provide the same clinical efficacy and spinal deformity correction as that of general anesthesia. Moreover, PKP surgery under local anesthesia can effectively reduce anesthesia-related complications such as cardiopulmonary system, allowing patients to get out of bed early and reduce hospitalization time and medical expenses [17]. Fang et al indicated that the type of anesthesia administered does not affect the clinical efficacy of PKP [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Local anesthesia can provide the same clinical e cacy and spinal deformity correction as that of general anesthesia. Moreover, PKP surgery under local anesthesia can effectively reduce anesthesia-related complications such as cardiopulmonary system, allowing patients to get out of bed early and reduce hospitalization time and medical expenses [13]. Fang et al indicated that the type of anesthesia administered does not affect the clinical e cacy of PKP [14].…”
Section: Discussionmentioning
confidence: 99%
“…However, when patients with m-OVFs receive local anesthesia, uoroscopy time often has to be increased, the operative time has to be extended, or the operation has to be terminated because of body posture-related discomfort, excessive local anesthetic drugs, the toxic reaction of bone cement, and abrupt uctuation of vital signs. The literature shows that the type of anesthesia method does not affect the e cacy of PKP for a single OVF, and general anesthesia increases the incidence of complications and medical costs [10,[13][14]. No relevant study has thus far been conducted on the choice of the type of anesthesia to administer to patients undergoing PKP for m-OVFs.…”
Section: Introductionmentioning
confidence: 99%